(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
One of the most crucial requirements for effective traffic management in cities is route optimization. Geographical information system (GIS) spatial analysis technique is important for route optimization. Route optimization involves not only finding the shortest path, but also properly increasing the route’s full efficiency. It is essential to use advanced traffic management techniques. Initially, reconnaissance survey was conducted in the study area to locate the congested locations and during the survey 3 locations were selected out of which one location was selected for traffic volume studies. The traffic volume survey was conducted in this study at the selected location where the transit system fails to meet its requirements. The spatial location information was collected using a global positioning system (GPS). The base map and various thematic maps were created using satellite imagery. Using GIS analysis, the causes of the transit issues were revealed, and alternative routes were proposed. . This study shows that overall number of cars travelling through Srinagar and its surrounding areas has expanded dramatically in recent years, resulting in increasing traffic volume and thus increasing traffic congestion and a reduction in the transportation efficiency and system integrity.